Analyse the Study of Media Violence on School Students - Mamta Vyas, P Bharath Babu (Mathematical Statistician and Engineering Applications, 2022)
Now more than ever, violence is an accepted element of daily life. The literature on this topic overwhelmingly demonstrates a correlation between exposure to media violence and aggressive behaviour in youngsters. Research has also demonstrated that exposure to violent media can quickly escalate aggressive tendencies. Video game critics counter that not all people who watch violent TV shows become violent themselves. Studies have found that students who regularly spend four or more hours a day watching violent media perform worse. It has been seen that exposure to violent media might toughen up and desensitise youth, which in turn may lead to aggressive behaviour. This is a first exploratory effort using questionnaires given to classroom instructors. In order to corroborate the findings, some of the teachers at a school in Surrounding Hyderabad in Telangana State were also interviewed. The study’s findings can be used to address the problem of violence in schools and guide future studies in this area.